Design and Implementation of BIM-Based Construction Supervision Platform for Hydraulic Engineering - YANG Chuhua; RAO Fanwei; FU Zhihao; LIAO Xiangjun (Renmin Zhujiang)
With the continuous promotion of high-quality development of water conservancy in the new era,it has become an inevitable trend to make full use of information technologies such as BIM,digital twins,and simulations to integrate and innovate with the water conservancy industry.In hydraulic engineering,an intelligent management system focusing on “BIM+a whole life cycle” has been gradually formed.Centering on the construction stage of hydraulic engineering,this study uses the new generation of information technologies such as BIM,big data,3S,and three-dimensional (3D) visualization to build an advanced,practical,and safe construction supervision platform for hydraulic engineering that can integrate the basic and overall construction process information resources.It is expected that the platform can greatly reduce the risks and solve the problems such as insufficient cooperation among institutions,difficult information collection,poor data sharing and consistency,and low construction management efficiency. In this way,we can realize the all-round dynamic supervision of project construction,strengthen the whole-process integration of project information,and promotes the visual,integrated,and collaborative management of project quality,safety,progress,costs,and archives. In the end,this research can provide technical support for the fine and efficient management of hydraulic engineering.